2017
DOI: 10.1177/1010428317691191
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of a novel long noncoding RNA TRPM2-AS promotes apoptosis in non–small cell lung cancer

Abstract: Non–small cell lung cancer is one of the most common types of cancer, and the prognosis of non–small cell lung cancer is still poor. Recent evidence has proved that long noncoding RNA is involved in tumorigenesis. For non–small cell lung cancer, the expression profile of long noncoding RNA has been studied. Here, we identified a novel long noncoding RNA TRPM2-AS from published dataset and found TRPM2-AS is widely upregulated in non–small cell lung cancer tissues compared with adjacent non-tumor tissues. Higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…TRPM2-AS is an antisense lncRNA mapped to 44 658 901-44 669 874 position of TRPM2 gene (Orfanelli et al, 2008). It was demonstrated to be an oncogene for non-small-cell lung cancer, prostate cancer, and hepatocellular carcinoma (Huang et al, 2017;Orfanelli et al, 2015;Xu et al, 2018). However, its effects in gliomas are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TRPM2-AS is an antisense lncRNA mapped to 44 658 901-44 669 874 position of TRPM2 gene (Orfanelli et al, 2008). It was demonstrated to be an oncogene for non-small-cell lung cancer, prostate cancer, and hepatocellular carcinoma (Huang et al, 2017;Orfanelli et al, 2015;Xu et al, 2018). However, its effects in gliomas are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Studies found the presence of TRPM2‐AS activation in many carcinomas, such as melanoma (Orfanelli et al, ), lung cancer (Huang et al, ), and prostate cancer (Mouraviev et al, ). Downregulation of TRPM2‐AS prompted apoptosis and interfered with the cisplatin resistance in non‐small‐cell lung cancer (Huang et al, ; Ma et al, ). However, its roles in cancer metastasis and its roles in gliomas remain unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…lncRNA TRPM2-AS, which is an antisense lncRNA of TRPM2, is 875 nt in length and located in the chr21q22.3 locus [13]. TRPM2-AS was first studied in prostate cancer [13] and then studied in the context of non-small cell lung cancer (NSCLC), where it was found to be related to the survival of NSCLC patients and chemoresistance in NSCLC [14,15]. However, until now, the role of lncRNA TRPM2-AS in HCC has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 TRPM2-AS locates at human chr21q22.3, and consists of 875 nucleotides with three exons in the translation template. 12 TRPM2-AS has been revealed to be upregulated and involved in the progression of melanoma, 12 non-small cell lung cancer, 13,14 hepatocellular carcinoma, 15 and prostate cancer. [16][17][18] The expression status and function of TRPM2-AS were still in osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%